The Migration-Poverty Trap: Assessing Farm Output and Household Welfare in Rural Nigeria - Nwofoke, Christian; Baya, Baynachew Bargissa; Odom, C.N.; Rosemary, Nwobegu (LPPM Universitas Jambi, 2025)
This study evaluates the impact of rural migration on the poverty status of farming households in Akure South, Nigeria. Using a multi-stage sampling technique to survey 120 respondents, the research employed descriptive and inferential statistics to analyze migration dynamics. Findings indicate that migration is primarily driven by education and skill acquisition, influenced by social expectations, land reforms, and poor institutional access. Notably, the study reveals a paradoxical decline in agricultural productivity and income following member migration. This reduction is driven by a 68.3 percent increase in labor costs and a significant decrease in cultivated land. Statistical analysis confirms that migration negatively affects farm output and total income, leading to the rejection of the null hypothesis. The research highlights a labor drain effect where human capital flight inadvertently exacerbates rural economic vulnerability. These results imply that without strategic interventions such as mechanization and improved infrastructure, migration will continue to undermine smallholder productivity. Consequently, policy frameworks must balance labor mobility with rural developmental support to mitigate poverty effectively.